First report of tethered cord syndrome in a patient with Sotos syndrome - Pelin Kuzucu; Tolga Türkmen; Alp Özgün Börcek (BMC, 2020)
Abstract Background Sotos syndrome is caused by a gene deletion with an autosomal dominant pattern of inheritance. The Sotos syndrome was first described by Juan Sotos. Cole and Hughes identified the clinical characteristics of this syndrome. This syndrome is characterized by macrocephaly, frontal bossing, ocular hypertelorism, overgrowth, subdural hygroma, ventricular dilatation, agenesis of the corpus callosum. This syndrome is associated with mutations in NSD 1 (nuclear receptor SET domain-containing protein 1) gene, protein insufficiency, and a 5q35 microdeletion. Sotos syndrome is reported to occur in approximately 1/10,000-15,000 births. Case presentation We present a patient with Sotos syndrome who is harboring a sacral lipoma and tethered cord syndrome and she had growth retardation, frontal bossing and hypertelorism. After a standard approach for tethered cord syndrome, the patient was discharged 3 days after without any additional neurodeficits. Conclusion In the literature, sacral lipoma and tethered cord syndrome with Sotos syndrome have not been published yet.